Penerapan Metode VIKOR Dalam Penentuan Penerima Dana Bantuan Rumah Tidak Layak Huni - Hotmoko Tumanggor; Mardiana Haloho; Putri Ramadhani; Surya Darma Nasution (STMIK Budi Darma, 2018)
The provision of grants is a program given by the government to the less fortunate. A grant program is held to assist the community in the survival of the community, especially in housing issues. The provision of home assistance is done selectively in accordance with the assistance provided. One of the help offered is uninhabitable Home Assistance (RUTILAHU). In this study used the VIKOR method so that the results obtained are expected to assist the government in managing the RUTILAHU Relief Fund to decide the eligible beneficiaries.